Profile and characteristic of laryngeal cancer in Radiotherapy Department of Hasan Sadikin General Hospital - Pinakaratna, Afifah; Utama, Marhendra Satria; Permana, Agung Dinasti (Oto Rhino Laryngologica Indonesiana, 2023)
Background: A laryngeal cancer diagnosis is often in the advanced stage, while the screening has not much done at this time. Studies on laryngeal cancer that uses radiotherapy are also still difficult to find, especially in Indonesia. Purposes: This study aimed to describe patients' profiles with laryngeal cancer who received radiotherapy treatment in the 2018 to 2019 period. Methods: This research was a descriptive quantitative with a cross-sectional study conducted at Radiotherapy Department, Hasan Sadikin General Hospital. Results: The patient's medical record was collected, and 38 patients with laryngeal cancer were found. Most of the patients are male (86,8%), ranging from age 51-60 (55,3%), work as staff office/traders (21,1%), and have a smoking history (52%). The chief complaint is often in the form of hoarseness (76,3%), the location of the cancer is No Other Specified (31,6%), most of the cells were squamous cell carcinoma (86,8%), and the stage was mainly in stage IV (60,5%). Surgery with radiotherapy is the most common management (50%), and surgery that is commonly used is total laryngectomy (36,8%). Some patients also have a tracheostomy before management (36,8%). Radiotherapy is more often for adjuvant purposes (52,6%). Conclusions: Laryngeal cancer is still uncommon, but we need to increase awareness and screening because of the advanced stage that more commonly occurs.